Roles of estrogen and its receptors in polycystic ovary syndrome - Xu, Yao; Zhang, Ziyi; Wang, Rongxiang; Xue, Songguo; Ying, Qian; Jin, Liping (Frontiers in Cell and Developmental Biology, 2024)
Polycystic ovary syndrome (PCOS) is an endocrine disorder characterized by abnormal steroid hormone levels in peripheral blood and poor-quality oocytes. In the ovary, androgen is produced by theca cells, and estrogen is produced by granulosa cells. Androgen is converted to estrogen in granulosa cells, with cytochrome P450 aromatase as the limiting enzyme during this process. Estrogen receptors (ER) include ER alpha, ER beta, and membrane receptor GPR30. Studies have demonstrated that the abnormal functions of estrogen and its receptors and estradiol synthesis-related enzymes are closely related to PCOS. In recent years, some estrogen-related drugs have made significant progress in clinical application for subfertility with PCOS, such as letrozole and clomiphene. This article will elaborate on the recent advances in PCOS caused by abnormal expression of estrogen and its receptors and the application of related targeted small molecule drugs in clinical research and treatment.